Understanding Syllables to Improve English Speaking Skills - Putri, Suci Aisya; Wulandari, Wulandari; Farhansyah, Qoeddri; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
Syllables play a key role in shaping pronunciation and fluency for English as a Foreign Language (EFL) learners. Insufficient awareness of syllables can hinder learners’ ability to produce intelligible speech and affect their communication in academic and daily contexts. This study investigates how five fourth-semester students from the English Education Department at UIN Sumatera Utara identify English syllables through a phonological awareness task. Using a mixed-method approach involving descriptive analysis and interviews, the findings show that although students conceptually understand syllables, their accuracy in practical identification varies—especially with phonetically reduced or irregular words like "vegetable" and "chocolate." Participants used strategies such as clapping, oral segmentation, and visual guessing, but often relied too heavily on spelling. These results underscore the need for explicit, practical syllable-based instruction to help students develop greater fluency, pronunciation accuracy, and speaking confidence.